PERAN PENGURUS KOPERASI KONSUMEN AL-MUAWANAH SYARIAH DALAM UPAYA MENGEMBANGKAN MUAWANAH MART UINFAS BENGKULU - Atisa Prianti; Supardi Mursalin; Esti Alfiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to determine the role of the Al-Muawanah Syariah Consumer Cooperative Management in efforts to develop Muawanah Mart UINFAS Bengkulu. This study uses a qualitative research method. While data collection in this study uses an interview system, observation, and documentation. The results of this study, the form of role carried out by the management of the Al-Muawanah Syariah consumer cooperative, namely in terms of: (1) Capital (2) In terms of cooperation (3) Products (4) Planning in efforts to develop Muawanah Mart development carried out by the Al-Muawanah Syariah consumer cooperative are: (1) Promotion or Trying to continuously introduce this Muawanah Mart mini market to the community both verbally and through social media (2) Increasing the number of members and investment (3) Establishing cooperation through business partners of the Al-Muawanah Syariah Consumer Cooperative, the cooperative relationship between producers and this institution is one of the efforts made by the university to provide a forum for students to be able to create new innovations so as to produce a work of products or services that have high selling value.